Dynamical Systems in Engineering (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This collection of articles includes the latest results related to applications of dynamical systems in the mathematical modelling of engineering problems, such as those concerning power system dynamics, material science, energy systems, gas dynamical networks, etc.Its purpose is to bring together mathematicians with engineers and physicists, as well as other scientists. The articles accepted and included are of a high quality and have original research results.